Relicts from Tertiary Australasia: undescribed families and subfamilies of songbirds (Passeriformes) and their zoogeographic signal - Schodde, Richard; Christidis, Les (Zootaxa, 2014)
A number of hitherto unrecognized, deeply divergent taxa of Australasian songbirds have been revealed by DNA sequence studies in the last decade. Differentiation among them is at levels equivalent to family and subfamily rank among songbirds generally. Accordingly, the purpose of this paper is to name and describe eleven of them formally under Articles 13.1, 13.2, 16.1 and 16.2 of the International Code of Zoological Nomenclature so that they are made available for use in zoology. The taxa are: families Oreoicidae, Eulacestomatidae, Rhagologidae, Ifritidae and Melampittidae, and subfamilies Pachycareinae, Oreoscopinae, Toxorhamphinae, Oedistomatinae, Peltopsinae and Lamproliinae. The families to which the subfamilies belong are documented. Morphological and behavioural traits of the new family-group taxa are discussed; reasons for taxonomic rankings are summarized; and grounds for the geographic origin of corvoid songbirds, to which all the new families belong, are briefly addressed. One new genus,Megalampitta in Melampittidae, is also described.